2017
DOI: 10.11648/j.ijics.20170205.11
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Cyberbullying: Its Forms, Awareness and Moral Reasoning Among Youth

Abstract: This purpose of the study is to investigate forms, awareness and moral reasoning against cyberbullying among youth. The study used primary data which was obtained through self-administered survey questionnaire. A total of 120 questionnaires were distributed to three different universities to examine the behaviour of youth towards cyberbullying pattern. Descriptive, frequency and correlation analysis were carried out on the primary data gathered. Findings showed that the three independent variables have close r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Cyberbullying is a new form of bullying through internet technology that can be subcategorized into text messages, bullying, pictures, videos clips and phone calls (Asanan et al, 2017). The main actions of cyberbullying include threats, name-calling, social isolation, spreading rumours, and sharing private information (Johnsonet al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cyberbullying is a new form of bullying through internet technology that can be subcategorized into text messages, bullying, pictures, videos clips and phone calls (Asanan et al, 2017). The main actions of cyberbullying include threats, name-calling, social isolation, spreading rumours, and sharing private information (Johnsonet al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the costs which youngsters are paying is through the prevalence of bullying via electronic means. Cyberbullying has become one of the core issues of society [45]. It is defined as repetitive and deliberate aggression of an individual or a group using electronic communication tools [46], [47].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moral disengagement has always been studied as an antecedent of cyberbullying perpetration, and none of the studies has rationally analyzed moral disengagement in terms of cyberbullying perpetration. Moreover, the literature reveals that moral disengagement is having a positive impact over the cyberbullying perpetration [3] [51], [55]. The studies found that individuals who are high at moral disengagement are more likely to be included in a group of cyberbullies.…”
Section: B Socio-cognitive Factors and Cyberbullying Attitudementioning
confidence: 99%
“…However, the level of guilt and grief have a negative impact on the adoption of cyberbullying behaviour [48]. Moral disengagement [3] is a cognitive process through which people support their aggressive behaviour, and those individuals who accept or support normative beliefs related to cyberbullying are more likely to perform this behaviour [56]. Moral disengagement strengthens due to a lack of guilt [57] and grief.…”
Section: B Socio-cognitive Factors and Cyberbullying Attitudementioning
confidence: 99%
See 1 more Smart Citation